2005
DOI: 10.1074/jbc.m411864200
|View full text |Cite
|
Sign up to set email alerts
|

DNA Polymerase λ Mediates a Back-up Base Excision Repair Activity in Extracts of Mouse Embryonic Fibroblasts

Abstract: Mammalian DNA polymerase (pol) is a member of the X-family of DNA polymerases and has striking enzymatic and structural similarities to mammalian DNA pol ␤. Because pol ␤ provides two important enzymatic activities for base excision repair (BER), we examined whether pol might also contribute to BER. We used extracts from mouse embryonic fibroblasts representing wild-type and null genotypes for pol ␤ and pol . In combination with neutralizing antibodies against pol ␤ and pol , our results show a BER deficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
131
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(140 citation statements)
references
References 39 publications
(45 reference statements)
9
131
0
Order By: Relevance
“…Recently, it was also demonstrated that in addition to pol β, DNA polymerase λ (pol λ) and DNA polymerase ι (pol ι), as well as the mitochondrial polymerase pol γ have 5′dRP lyase activity and can function (in vitro) in the removal of the 5′ dRP group that arises during BER [53,[57][58][59][60][61]. This would suggest that pol ι and/or pol λ may participate in BER, possibly as a back-up to pol β or may function with unique lesion specificity, in-line with the proposition that the initiating lesion directs the repair sub-pathway [51,62].…”
Section: Nih Public Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was also demonstrated that in addition to pol β, DNA polymerase λ (pol λ) and DNA polymerase ι (pol ι), as well as the mitochondrial polymerase pol γ have 5′dRP lyase activity and can function (in vitro) in the removal of the 5′ dRP group that arises during BER [53,[57][58][59][60][61]. This would suggest that pol ι and/or pol λ may participate in BER, possibly as a back-up to pol β or may function with unique lesion specificity, in-line with the proposition that the initiating lesion directs the repair sub-pathway [51,62].…”
Section: Nih Public Accessmentioning
confidence: 99%
“…Although MEFs deficient in either pol ι or pol λ are not hypersensitive to alkylating agents [44], the ability of either pol ι and/or pol λ to complement pol β in vivo has not been evaluated. Using MEFs isolated from pol λ knockout mice [63], a back-up role for pol λ was observed following oxidative damage, although the requirement for the 5′dRP activity of pol λ has not been determined [53,59]. To date, a targeted deletion or inactivation of the mouse POLI gene has not been reported.…”
Section: Nih Public Accessmentioning
confidence: 99%
“…This flexibility was first suggested by the observation that Pol λ generates deletion errors at an extremely high rate [11], and is now thought to be a feature of the enzyme that facilitates its role in vivo. The phenotypes of mice deficient in this polymerase indicate that Pol λ plays a role in the V(D)J process of antigen gene diversification [12], and several reports implicate Pol λ in Base Excision Repair [13][14][15] and the repair of double-strand breaks through the Non-Homologous DNA End-Joining pathway [16][17][18]. It is thus interesting to examine the details of the polymerization reaction as catalyzed by Pol λ in order to understand whether specific catalytic features can account for these special properties.…”
Section: Introductionmentioning
confidence: 99%
“…Pol k acts as a backup for Pol b function in general BER [Braithwaite et al, 2005;Tano et al, 2007;Braithwaite et al, 2010], but has a specific role in BER of the oxidized base 8-oxo-deoxyguanine (8-oxoG). Together with cofactors replication protein A and proliferating cell nuclear antigen, Pol k is the mammalian polymerase most able to correctly incorporate dC opposite 8-oxoG [Maga et al, 2007].…”
Section: Pol Kmentioning
confidence: 99%